Postembryonic lineages of the Drosophila ventral nervous system: Neuroglian expression reveals the adult hemilineage associated fiber tracts in the adult thoracic neuromeres. Issue 13 (9th March 2016) - Shepherd, David; Harris, Robin; Williams, Darren W.; Truman, James W.
Abstract : During larval life most of the thoracic neuroblasts (NBs) in Drosophila undergo a second phase of neurogenesis to generate adult‐specific neurons that remain in an immature, developmentally stalled state until pupation. Using a combination of MARCM and immunostaining with a neurotactin antibody, Truman et al. (2004; Development 131:5167–5184) identified 24 adult‐specific NB lineages within each thoracic hemineuromere of the larval ventral nervous system (VNS), but because of the neurotactin labeling of lineage tracts disappearing early in metamorphosis, they were unable extend the identification of these lineages into the adult. Here we show that immunostaining with an antibody against the cell adhesion molecule neuroglian reveals the same larval secondary lineage projections through metamorphosis and bfy identifying each neuroglian‐positive tract at selected stages we have traced the larval hemilineage tracts for all three thoracic neuromeres through metamorphosis into the adult. To validate tract identifications we used the genetic toolkit developed by Harris et al. (2015; Elife 4) to preserve hemilineage‐specific GAL4 expression patterns from larval into the adult stage. The immortalized expression proved a powerful confirmation of the analysis of the neuroglian scaffold. This work has enabled us to directly link the secondary, larval NB lineages to their adult counterparts. The data provide an anatomical framework that 1) makes it possible to assign most neurons to their parent lineage and 2) allows more precise definitions of the neuronal organization of the adult VNS based in developmental units/rules. J. Comp. Neurol. 524:2677–2695, 2016. © 2016 The Authors The Journal of Comparative Neurology Published by Wiley Periodicals, Inc. Abstract : The authors show that Neuroglian expression in Drosophila can be used to trace thoracic larval neuronal lineages through metamorphosis. This has made it possible to link secondary, larval lineages to their adult counterparts and provide a framework that makes it possible to assign most neurons to their parent lineage.